Alterações de atributos de solos submetidos ao pousio em núcleo de desertificação - Ferreira, Mirele Paula da Silva (2015)
Soil degradation can occur because of inadequate management, which may result in soil unproductive and, in certain situations, lead to the desertification process. One of the causes of degradation is overgrazing, causing loss of biodiversity of plant strata by the pressure of ramoneio and soil compaction by excessive trampling of animals, bringing implications to the ground in the physical, chemical and biological properties, thereby undermining the sustainability of the agroecosystem. An alternative to recover soil degradation is the practice of fallow, because that is easy to perform and inexpensive to restore soil properties that provides input of organic matter, important soil conditioner. With that aimed to prove the hypothesis that the time of 14 year fallow improves the physical and chemical soil in degraded areas in the process of desertification. The areas selected for the study are located in the municipality of Irauçuba in the state of Ceará, Brazil. Soil samples were taken in five areas of overgrazing, in five areas of fallow and in a forest area, is serving as the reference area. Physical and chemical analysis of the soil as soil density, total porosity, flocculation, pH, electrical conductivity, cation exchange capacity (CTC), total organic carbon, carbon management index and physical fractions of organic carbon, were done to assess the changes the physical and chemical attributes of these areas. The management of fallow showed improvements in physical and chemical soil when assessed after 14 years of withdrawal of animals, but when compared to the work done in the same area in 2009, with 7 years of fallow, evidence that the areas are still in the process of degradation. The organic carbon content was higher in the areas of fallow and the fraction with the highest proportion was the organic carbon associated to minerals.